Nature‐Inspired 3D Spiral Grass Structured Graphene Quantum Dots/MXene Nanohybrids with Exceptional Photothermal‐Driven Pseudo‐Capacitance Improvement. Issue 30 (26th August 2022) - Chang, Peng; Mei, Hui; Zhao, Yu; Pan, Longkai; Zhang, Minggang; Wang, Xiao; Cheng, Laifei; Zhang, Litong
Abstract: Solar‐thermal conversion is considered as a green and simple means to improve the performance of energy storage materials, but often limited by the intrinsic photothermal properties of materials and crude structure design. Herein, inspired by the unique light trapping effect of wide leaf spiral grass during photosynthesis, a biomimetic structural photothermal energy storage system is developed, to further promote the solar thermal‐driven pseudo capacitance improvement. In this system, three‐dimensional printed tortional Kelvin cell arrays structure with interesting light trapping property functions as "spiral leaf blades" to improve the efficiency of light absorption, while graphene quantum dots/MXene nanohybrids with wide photothermal response range and strong electrochemical activity serve as "chloroplast" for photothermal conversion and energy storage. As expected, the biomimetic structure‐enhanced photothermal supercapacitor achieves an ideal solar thermal‐driven pseudo capacitance enhancement (up to 304%), an ultrahigh areal capacitance of 10.47 F cm −2, remarkable photothermal response (surface temperature change of 50.1 °C), excellent energy density (1.18 mWh cm −2 ) and cycling stability (10000 cycles). This work not only offers a novel enhancement strategy for photothermal applications, but also inspires new structure designs for multifunctional energy storage and conversion devices. Abstract : A biomimetic structural graphene quantum dots/MXene photothermal supercapacitor inspired by the light‐trapping effect of wide‐leaf spiral grass is developed. The novel bionic structural supercapacitor achieves remarkable photothermal response (surface temperature of 67.6 °C under one‐sun illumination) and record‐high solar thermal‐driven pseudo‐capacitance enhancement (up to 304% at high rate) that will open new frontiers for the application of solar thermal energy.